EVALUASI PEMBERIAN PROBIOTIK BACILLUS PADA MEDIA PEMELIHARAAN TERHADAP LAJU PERTUMBUHAN DAN PERUBAHAN HISTOPATOLOGI IKAN LELE DUMBO (Clarias gariepinus) YANG DIINFEKSI Aeromonas hydrophila - Angela Mariana Lusiastuti; Mohammad Faizal Ulkhaq; Widanarni Widanarni; Tri Heru Prihadi (Jurnal Riset Akuakultur, 2016)
The aim of this study was to evaluate the addition of a probiotic Bacillus on culture medium through growth rate and histopathological change in African Catfish who was infected by Aeromonas hydrophila. The study consisted of five treatments such as the addition of probiotic Bacillus ND2, Bacillus P4I2, Bacillus ND2 + Bacillus P4I2 (Kom), positive control (K+) and negative control (K-) (without probiotic addition). African Catfish (13.354±2.8 g) was maintained in 15 aquariums (40 L in volume) with 30 fishes each for 30 days. Probiotic bacteria was applied in water once a day, whereas pathogenic bacteria A. hydrophila  (103 CFU/mL) were added once in earlier treatment (except for the negative control) as assumption that A. hydrophila will shape up quorum sensing in unfortunate condition. The result showed that the highest spesific growth rate in the treatment of Bacillus ND2 probiotics (1,708 ± 0.114%). Histopathology showed that damaged of liver dan kidney in probiotics treatment were lightner than positive control (K+).  The addition of Bacillus P4I1 (104 CFU/mL) efective to increased the spesific growth rate of African Catfish and prevent the damage of liver and kidney of African Catfish was infected by Aeromoniasis.